"Alternative" materials in the green building and construction sector: Examples, barriers, and environmental analysis. Issue 4 (11th June 2019) - Krueger, Kate; Stoker, Adam; Gaustad, Gabrielle
Abstract : Purpose: The construction, use and demolition of buildings carry enormous environmental burdens. As one step to reduce a building's environmental impact, green building design guidelines and certification programs, such as Leadership in Energy and Environmental Design, Cradle to Cradle and the Whole Building Design Guide, promote the specification of alternative, non-traditional building materials. Alternative materials carry a variety of potential benefits: reducing the amount of energy and other resources needed to create building materials; creating healthier indoor and outdoor environments; diverting or reducing waste from landfills; reducing the use of scarce, critical or economically volatile materials; and spurring innovation in the building industry. However, a lack of clarity surrounds alternative materials and creates a barrier to their usage. The purpose of this paper is to review definitions of alternative materials in various design guidelines in order to provide context to their specification and usage. Design/methodology/approach: Through a survey of green building programs and guidelines, existing literature on alternative materials, and life-cycle assessment using multiple inventory databases, this study tackles the following questions: what constitutes an alternative building material; what are the current barriers to their specification; how are they specified in the most common design guidelines; and do alternative building materials present a "greener" alternative? Findings: These results show that while often alternative materials do in fact show promise for reducing environmental impacts of the built environment, by how much can be a challenging question to quantify and depends on a variety of factors. While many green building guides and certification systems provide recommendations for use of alternative materials, the sheer diversity and uncertainty of these systems coupled with the complexity in understanding their impacts still present a significant barrier to their specification. Much work remains in a variety of disciplines to tackle these barriers. A clear emphasis should be on better understanding their environmental impacts, particularly with respect to the context within the built environment that their specification will provide energy, resource and emission savings. Other key areas of significant work include reducing costs, removing regulatory and code barriers, and educating designers, consumers, and end-users. Originality/value: Alternative materials are defined and specified in a diversity of contexts leaving the design and construction communities hesitant to promote their use; other work has found this to be a key barrier to their widespread usage. By compiling definitions, barriers and design guidelines instructions while also exploring analytically the benefits of specific cases, this work provides a foundation for better understanding where new, more sustainable materials can be successfully specified.